A Biomass-Based Redox Gel Polymer Electrolyte for Improving Energy Density of Flexible Supercapacitor. Issue 10 (1st January 2019) - Xun, Zhiyu; Liu, Yang; Gu, Jiyou; Liu, Lingxiao; Huo, Pengfei
Abstract : Energy density is a critical issue for an energy storage device. In this paper, A series of gel polymer electrolytes were prepared. The renewable soy protein isolate (SPI) was selected as the polymer matrix, Li2 SO4  was used as the neutral electrolyte salt to obtain a wider potential window (1.5 V), and the redox mediator KI was introduced to elevate the energy density of the flexible supercapacitor assembled with the prepared gel polymer electrolyte sandwiched by activated carbon electrodes. The performances of the supercapacitor with an optimized SPI- Li2 SO4 -KI gel polymer electrolytes were evaluated by physical characterization analysis (SEM, FT-IR, XRD, Raman) and electrochemical analysis (CV, GCD, EIS). With the addition of KI mediator, the ionic conductivity of gel polymer electrolyte was increased, the electrochemical series resistance of the supercapacitor was reduced, and the pseudocapacitance could be observed. The electrode specific capacitance of the supercapacitor with SPI-Li2 SO4 -100 wt% KI electrolyte is 224.19 F g −1, increasing by 156% compared to the SPI-Li2 SO4  system at the same current density. Meanwhile, the energy density of the supercapacitor increases from 5.90 to 16.02 W h kg −1 . In addition, the quasi-solid-state supercapacitor showed excellent flexibility and considerable application.